Översättaren och ordboken - Gellerstam, Martin (Nordiske Studier i Leksikografi, 1997)
It seems obvious that translators will need dictionaries in the process of translating. But dictionmy use will differ according to the direction of the translation, the translator’ s competence and text register. In this paper, the active bilingual dictionary used by the non-professional translator is focused and its shortcomings are discussed. The need of corpus data, notably parallell texts, is pointed out as a complement to the bilingual dictionmy. The case is demonstrated by a comparison between equivalents recommended in a comprehensive bilingual Swedish dictionary and corpus data from parallell texts.